[quotation] On awareness - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'Those of us who are aware should stop failing our fellow citizens and work diligently towards informing them and educating them on the fragility of our environment. Only through increased awareness will the agenda of economic profits be replaced by...